A Novel Dental Plaque Index Using Intraoral Camera Images - Ji-Soo Kim (The Korean Society of Dental Hygiene Science, 2024)
Background: This study aimed to evaluate whether a Novel Plaque Index (NPI) using intraoral camera images would be more useful for assessing the accumulated area of dental plaque compared to three other indices. Methods: This study evaluated 80 disclosed plaque tooth surface images from 40 participants, including the facial surfaces of the maxillary left first molar and mandibular left central incisor. The tooth surface was divided longitudinally into three sections, with each section further subdivided into four subsections. A score ranging from 0 to 5 was assigned to each longitudinal third, and the average score was determined as the NPI score for the tooth surface. Two examiners assessed the NPI, Patient Hygiene Performance Index, Quigley and Hein Plaque Index, and Rustogi's Modified Navy Plaque Index scores obtained using the plaque images. The assessments were repeated twice with a 2-weeks washout period. The Plaque Percent Index (PPI) score calculated via image analysis is considered the gold standard. Results: The NPI showed the highest correlation coefficient with PPI compared to the other indices (examiner 1: 0.87, examiner 2: 0.88). The intraexaminer reliability of the NPI was excellent for both examiners. The intraclass correlation coefficient (ICC) for examiner 1 and 2 was 0.95 and 0.93, respectively. The weighted kappa values were ＞0.85 for both examiners. The ICC of the interexaminer analysis was 0.93 and the weighted kappa showed a reliability value of 0.81. Conclusion: The NPI was found to have greater validity and reliability than the three existing indices for the quantitative scoring of dental plaque.